2019
DOI: 10.1007/s42978-019-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Career Performance Progressions of Junior and Senior Elite Track and Field Athletes

Abstract: Purpose To compare and assess differences in the career performance progressions of elite junior and Olympic track and field athletes. Methods Annual best performances from top 8 men and women (e.g. finalists) in track and field events at the 2000 World Junior Championships (junior cohort) and the 2000 Olympic Games (Olympic cohort) were examined. Annual bests of these finalists were tracked each year from select groups: sprints (100 m, 200 m), distance (1500 m, 5000 m), jumps (long jump, high jump), throws (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 29 publications
2
21
1
Order By: Relevance
“…This is in agreement with the findings of Svendsen et al (2018), who found that the strongest predictor of senior success among Norwegian junior road cyclists was race performance at 18 years of age. However, it is in contrast to the findings of Foss, Sinex, and Chapman [ 1 ], who, after finding that World Junior Championship finalists in athletics reached their career-best performance at an earlier age and had less performance improvements during their careers than Olympic Games finalists, challenged the assertion that elite success at junior level is a prerequisite for success at senior level. It has to be underlined that, despite the fact that the Norwegian international champions listed in Table 3 showed excellent performance at the age of 18 years, only one of them (JI) won an international title at U20.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This is in agreement with the findings of Svendsen et al (2018), who found that the strongest predictor of senior success among Norwegian junior road cyclists was race performance at 18 years of age. However, it is in contrast to the findings of Foss, Sinex, and Chapman [ 1 ], who, after finding that World Junior Championship finalists in athletics reached their career-best performance at an earlier age and had less performance improvements during their careers than Olympic Games finalists, challenged the assertion that elite success at junior level is a prerequisite for success at senior level. It has to be underlined that, despite the fact that the Norwegian international champions listed in Table 3 showed excellent performance at the age of 18 years, only one of them (JI) won an international title at U20.…”
Section: Discussioncontrasting
confidence: 65%
“…Exceptional sporting performance, often defined as winning a medal in an international competition, is dependent on motor and physical development over the lifespan [ 1 ]. Today, children often focus on training and competition in sports from an early age, in the hope that this will help them to reach an elite level as adults [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings thus corroborate previous evidence suggesting that talent identification and selection at young ages can be biased and do not guarantee the ability to identify senior performers in athletics. 19,23,24,36 Also, as already observed in sprinter athletes, 37 young jumpers that reach a high-performance level without excessive specialization may have a better development toward senior success.…”
mentioning
confidence: 78%
“…23 At the moment, there is no clear information on typical transition rates for world-class jumpers. 24 The only way to analyze this aspect would be to assess the performances of a large sample of world-class athletes and track their development across their whole sporting career.…”
Section: Introductionmentioning
confidence: 99%